Preservation of Sacred Traditions in Heritage Tourism in Bali: Between Commercialization and Sacredness - Ni Komang Fitri Suarnadi; Nyoman Diah Utari Dewi; Ni Putu Tirka Widanti (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Heritage tourism in Bali is a strategic sector that not only underpins the regional economy but also plays a critical role in safeguarding the cultural identity of local communities. Bali is globally recognized for its rich tangible heritage, including temples, traditional architecture, and customary villages, as well as its intangible heritage, such as religious rituals, performing arts, and local craftsmanship. This study aims to analyze the governance dynamics of heritage tourism in Bali by highlighting the roles of local communities, government policies, and the pressures of globalization and cultural commodification. The research adopts a qualitative approach through a literature review and case study analysis of key destinations, including Besakih Temple, Tanah Lot, Uluwatu, Penglipuran Village, and traditional performances such as the Kecak and Barong dances. The findings indicate that heritage tourism generates significant economic value through job creation and the growth of the creative economy, while simultaneously strengthening Bali’s cultural diplomacy at the international level. However, challenges such as overtourism, unequal benefit distribution, and environmental degradation necessitate a more sustainable management framework. The strategies identified include strengthening community-based tourism, enforcing strict development regulations, educating tourists on Balinese cultural values, and leveraging digitalization for heritage promotion and preservation. By adopting a holistic, community-centered approach, heritage tourism in Bali can function as a scalable instrument for sustainable development while maintaining cultural authenticity. Keywords: Bali, Culture, Customary Villages, Heritage Tourism, Sustainable Tourism